Synthesis and Characterization of Mixed Ligand Complexes of Some Lanthanide(III) with N,N’-Triethylenediamine-bis-(3-carboxypropenamide) - Viswanathan, M.; Krishnan, G. (Asian Journal of Chemistry, 2012)
A series of mixed ligand complexes of lanthanide ions with N,N’-triethylenediamine-bis-(3- carboxypropenamide) have been synthesized and characterized by chemical analysis, conductance, magnetic, thermal and infrared spectral studies. On the basis of the above studies, the following general formula is suggested with a coordination number seven for these complexes: [M(TEBCP)X], where M = Pr(III), Nd(III), Sm(III), Gd(III) or Dy(III) and X = NO3–, Cl–, ClO4– or SCN–.